The nature of the firm : (Oxford University Press, 1991)
This volume derives from a conference held in 1987 to commemorate the fiftieth anniversary of the publication of Coase's classic article. The first chapter affords an overview of the volume. It is followed by a republication of the 1937 article, and by the three lectures Coase presented at the conference. These lectures provide a lively and informative history of the origins and development of his thought. Subsequent chapters explore a wide-range of theoretical and empirical issues that have arisen in the transaction cost economic tradition.